PENGARUH PENDIDIKAN GIZI TERHADAP SIKAP, ASUPAN ZAT GIZI MAKRO, DAN AIR PADA ANGGOTA PRAMUKA - Farida, Farida; Sari, Hesti Permata; Sulistyaning, Afina Rachma; Zaki, Ibnu (Universitas Islam Negeri Walisongo Semarang, 2019)
The study was aimed to analyze the effect of nutritional education on attitude changes and increased of macronutrients and water intake in scout teenagers. The study was quasi-experimental with pre- and post-test control group design. The treatment group was given nutritional education four times during one month. Pre-test was conducted a week before intervention and post-test was conducted a week after intervention. Subjects were all members of Saka Bhayangkara and Saka Wira Kartika Scout. The result showed that nutritional education was significant improved median value of attitude score and increased (p <0,05). macronutrients intake in treatment group. The average of macronutrients intake in treatment group, before and after intervention were 1137,8±178,7 Kcal and 1490,4± 206,6 Kcal/day for energy; 40,4 ± 9,8 g/day and 60,8 ± 9,3g/day for protein; 38,5 ± 12,6 g/day and 59,3 ± 9,4 g/day for fat; 155,6 ± 29,5 g/day and 177,6 ± 33,5 g/day for carbohydrates; 782,4±347,7 mL and 834,6±383,2 mL for water. Nutritional education improved nutrition attitudes and increased macro-nutrient intake among scout.